Influence of Thyroid Stimulating Hormone on Liver Enzymes Levels in Serum of Thyroid Disorder Iraqi Patients - Samir , Qutaiba; Hameed , Marwa (Al-Nahrain Journal of Science, 2019)
Thyroid hormones are essential element in body growth and influence the formation of many enzymatic proteins. These hormones regulate and have a major role in controlling the metabolism of the entire body. They also play an important role in the normal hepatic function. Thyroid diseases are linked with liver enzymes levels irregularities, cholestatic jaundice resulted from low bilirubin level and bile excretion, hepatic lipid homeostasis, viral hepatitis, an increase in alanine aminotransferase, aspartate transferase and alkaline phosphatase. Thyroid stimulating hormone and serum liver enzymes were analyzed using standard kits. Results showed that hyperthyroidism and hypothyroidism patients had an elevation in the levels of serum alkaline phosphatase, aspartate transferase and alanine aminotransferase when compared to controls. However, the values were higher in hyperthyroidism patients. This work aims to study the effect of thyroid stimulating hormone on the level of liver enzymes in a group of local Iraqi patients with thyroid disorder.